2013
DOI: 10.1016/j.biortech.2013.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Using olive mill wastewater to improve performance in producing electricity from domestic wastewater by using single-chamber microbial fuel cell

Abstract: h i g h l i g h t sOlive mill wastewater (OMW) represents a problem for its disposal and treatment. Single-chamber MFC was used to produce electricity from OMW and wastewater (DW). MFCs fed with DW plus OMW gave 0.38 V (1 kO) and a power density of 124.6 mW m À2 . TCOD and BOD 5 of DW plus OMW mix was reduced of 65% and 50% respectively. Microbial characterization of electrodes bacterial communities indicate anode differences. Improving electricity generation from wastewater (DW) by using olive mill wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 31 publications
0
33
0
2
Order By: Relevance
“…In this line, a single-chamber MFC was used to test domestic wastewater mixed with olive mill wastewater (14:1, w/w) as anodic substrate [134]. This medium produced 0.38 V at 1 kΩ, which is 2.9 times higher than when using domestic wastewater, and a power density of 124.6 mW·m −2 .…”
Section: Microbial Fuel Cells For Wastewater Treatmentmentioning
confidence: 99%
“…In this line, a single-chamber MFC was used to test domestic wastewater mixed with olive mill wastewater (14:1, w/w) as anodic substrate [134]. This medium produced 0.38 V at 1 kΩ, which is 2.9 times higher than when using domestic wastewater, and a power density of 124.6 mW·m −2 .…”
Section: Microbial Fuel Cells For Wastewater Treatmentmentioning
confidence: 99%
“…Maximum COD and Biological Oxygen Demand (BOD 5 ) removal efficiencies of 65% and 50% respectively were reported in a single-chamber air cathode BES with platinum anode treating classical olive mill wastewater diluted with domestic wastewater at the ratio of 1:14 (COD: 4300 mg/L). DNA-fingerprinting showed the high bacterial diversity and the presence of exoelectrogenic bacteria on anodes, such as Geobacter spp (Sciarria et al, 2013).…”
Section: Olive Oil Washing Water Feedingmentioning
confidence: 99%
“…The use of microorganisms to catalyze the electrochemical oxidation of organics is highly attractive as it allows taking advantage of the versatility and resilience which bacteria exert. Responsible for the process are specific bacterial species, the so-called "exoelectrogens", mainly belonging to the gammaand delta-subgroups of Proteobacteria (Sciarria et al, 2013). The potential of BESs is enormous since this technology has important operational and functional advantages over the current technologies used for generating energy and valuable compounds from organic matter (Hernández-Fernández et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A microbial fuel cell is a bioreactor that can convert the chemical energy of organic compounds into electrical energy through exoelectrogenic bacterial species metabolism [14]. MFC technology is commonly used in urban wastewater treatment facilities to break down organic matter and produce electrical energy [15] but recently some authors have reported good performances using MFCs for agro-industrial wastewater treatment, for instance beer wastewater [16], swine manure [17] or olive mill wastewater [18].…”
Section: Introductionmentioning
confidence: 99%